Integrative analysis of chloroplast genome, chemicals, and illustrations in Bencao literature provides insights into the medicinal value of Peucedanum huangshanense - Sun, Haibing; Chu, Shanshan; Jiang, Lu; Tong, Zhenzhen; Cheng, Ming’en; Peng, Huasheng; Huang, Luqi (Frontiers in Plant Science, 2023)
The genus Peucedanum L. (Apiaceae) is a large group comprising more than 120 species distributed worldwide. Many plants of the genus Peucedanum have been studied and used in traditional Chinese medicine. In 2020, a new species, Peucedanum huangshanense Lu Q. Huang, H. S. Peng & S. S. Chu, was found in the Huangshan Mountains of Anhui Province, China. However, little is known about its medicinal properties. Thus, the objective of this study is to explore the potential medicinal value of P. huangshanense and its relationship with other Peucedanum species. Through textual research on illustrations of Qianhu in the Materia Medica, it can be inferred that at least five species of genus Peucedanum have been used in Chinese medicine. Therefore, we chose these five species of Peucedanum and P. huangshanense together for subsequent research. We conducted morphological, chloroplast genome, and chemical analyses of six Peucedanum species, including the newly discovered P. huangshanense. The chloroplast genomes of Peucedanum showed a typical tetrad structure, and the gene structure and content were similar and conservative. There were significant differences in genome size and the expansion of the inverted repeat boundary. Through nucleotide polymorphism analysis, we screened 14 hotspot mutation regions that have the potential to be used as specific molecular markers for the taxonomy of Peucedanum. Our results showed an inversion of the trnD-trnY-trnE gene in the P. huangshanense chloroplast genome, which can be developed as a specific molecular marker for species identification. Phylogenetic analysis showed that the phylogenetic trees had high support and resolution, which strongly supports the view that Peucedanum is not a monophyletic group. P. huangshanense had the closest genetic relationship to P. ampliatum K. T. Fu, followed by P. harry-smithii Fedde ex Wolff. Furthermore, the main coumarins of P. huangshanense were most similar to those of P. japonicum Thunb. and P. harry-smithii. In summary, our research lays a foundation for the systematic classification of Peucedanum and sheds light on the medicinal value of P. huangshanense.